Causality between insulin use and malignant tumors of the digestive system: a two-sample mendelian randomized study - DengZhuo Chen; YongLi Ma; JingHui Li; Liang Wen; GuoSheng Zhang; ChengZhi Huang; XueQing Yao (BMC Cancer)
Abstract Background Existing cohort studies show no association between insulin use and cancers of the digestive system, while numerous meta-analyses suggest that insulin use increases the risk of digestive system tumours. This study uses two-sample Mendelian randomization (MR) to further investigate the causal relationship between the two. Methods We selected single nucleotide polymorphisms (SNPs) strongly associated with insulin use as instrumental variables and used aggregated statistics on digestive system neoplasms as the outcome event. The primary method of analysis was inverse variance weighting (IVW), supplemented by weighted median, MR-Egger regression, weighted mode and simple mode methods. The reliability of the study was assessed by heterogeneity testing, pleiotropy analysis and sensitivity analysis. Result A total of 8 SNPs associated with insulin use were included as instrumental variables. Random-effects IVW analysis showed an association between insulin use and increased risk of colorectal cancer (OR = 1.1037, 95%CI = 1.0183–1.1962, P = 0.016). No statistically significant association was found between insulin use and the development of other digestive system tumours. The results were unaffected by pleiotropy and heterogeneity, and the reliability of the findings was confirmed by sensitivity analysis. Conclusion Our Mendelian randomization study suggests an association between insulin use and an increased risk of CRC, with no clear association observed for other digestive system tumours. However, further MR studies with larger sample sizes from genome-wide association study (GWAS) data are needed to verify this association.